Impacts of Ambient Brightness Control and Short-Wavelength Spectral Content on Display Screen User Responses - Bullough, John D. (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Brawijaya, 2024)
The computer display screen is an increasingly important and ubiquitous part of the modern visual environment. The photometric and colorimetric characteristics of computer display screens can have important consequences for the performance, visual fatigue and visual comfort of users. In the present study, two aspects of display screen performance were evaluated in terms of objective and subjective outcomes: an ambient brightness control designed to adjust the display luminance to the ambient lighting conditions in the space, and reduced short-wavelength spectral content designed to minimize visual discomfort and fatigue associated with this spectral region. The results indicate that the tested visual display functions yielded several measurable improvements compared to a display without these functions.